The lost intrauterine device: removal by hysterectomy. Issue 3 (1st July 2004) - Byrd, Louise; Slade, R
Abstract : A case of migration of an intrauterine device (IUD) deep within the endometrium, presenting as heavy vaginal bleeding and abdominal pain, is discussed. The IUD had been in situ for 31 years. Standard retrieval techniques failed and removal necessitated hysterectomy. The complications of 'lost IUDs' are discussed and the need to enquire about removal in all women on approaching the menopause is emphasised.